Expression of furfural reductase improved furfural tolerance in Antarctic bacterium pseudomonas extremaustralis - Ahmad Bazli Ramzi; Matthlessa Matthew Minggu; Ummul Syafiqah Ruslan; Mohamad Hazwan Fikri Khairi; Peer Mohamed Abdul (Penerbit Universiti Kebangsaan Malaysia, 2022)
Whole-cell biocatalysis using Antarctic bacteria is presently hampered by a lack of genetic information, limited gene tools and critically, a poor range of cultivation conditions. In this work, biological engineering strategy was employed for developing Pseudomonas extremaustralis, a metabolically-versatile and biopolymer-producing Antarctic bacterium, as a new whole-cell biocatalytic host. For this purpose, gene cloning and plasmid construction were carried out for overexpression of furfural reductase (FucO), an industrially-important enzyme for degradation of toxic furfural compound commonly found in lignocellulosic biorefinery. FucO gene from Escherichia coli BL21 was cloned in pJM105 plasmid and transformed into competent cells of P. extremaustralis to generate a biologically-engineered pFucO strain. For functional characterization of the enzyme, furfural reductase activity was assayed, where the P. extremaustralis pFucO strain exhibited increased furfural reductase activity of about 15.6 U/mg, an 18.8-fold higher than empty plasmid-carrying control pJM105 strain (0.83 U/mg). Furfural detoxification activity using whole cells was also determined by which the overexpression of FucO led to increased tolerance and cell growth with an OD600 value of 5.3 as compared to the control pJM105 strain that was inhibited with 10 mM furfural during 48-hour cultivation. Therefore, the findings obtained in this study successfully demonstrated the development of P. extremaustralis as biocatalytic host for the production of recombinant furfural reductase. The bioengineering would serve as a modular biotechnological platform for polar strain and bioproduct development tailored towards industrial biotechnology applications.